Adsorption of glutamic acid on clean and hydroxylated rutile TiO2(110): an XPS and NEXAFS investigation. (6th July 2022) - Carraro, Giovanni; Smerieri, Marco; Passaglia, Simone; Bracco, Gianangelo; Vattuone, Luca; Rocca, Mario; Cossaro, Albano; Verdini, Alberto; Floreano, Luca; Savio, Letizia
Abstract: Due to its biocompatibility, TiO2 is a relevant material for the study of bio-interfaces. Its electronic and chemical properties are influenced by defects, which mainly consist of oxygen vacancies or adsorbed OH groups and which affect, consequently, also the interaction with biological molecules. Here we report on an x-ray photoemission spectroscopy and near edge adsorption fine structure study of glutamic acid (Glu) adsorption on the rutile TiO2 (110) surface, either clean or partially hydroxylated. We show that Glu anchors to the surface through a carboxylate group and that the final adsorption state is influenced by the presence of hydroxyl groups on the surface prior to Glu deposition. Indeed, molecules adsorb both in the anionic and in the zwitterionic form, the former species being favored on the hydroxylated substrate.